Masquelet technique for infected femur bone defect in low resource setting: a case report - Simatupang, Mario D.; Ario, Stevanus I. (International Journal of Research in Orthopaedics, 2024)
Our hospital is located on the east edge of Indonesia, in the rural city of Merauke, South Papua. In this setting, procedures to bridge large bone defects are limited. The Masquelet technique is a two-stage orthopaedic procedure to treat large bone defects. This technique has a promising future for treating large bone defects, especially in low-resource settings. A 27 years old male experienced a traffic accident. The patient went unconscious and was brought to a nearby hospital where he underwent open reduction and internal fixation of his right femur open fracture. In the 4th week after the trauma, he was diagnosed with osteomyelitis. After multiple procedures in other hospitals, in the 74th week, he arrived at our hospital in Merauke, South Papua. We used Masquelet technique to bridge the bone gap and treat the osteomyelitis. In the first stage, we did debridement and sequesterectomy, then filled the bone defect with antibiotic impregnated PMMA spacer. After 5 weeks, the infection had subsided and the second stage of Masquelet technique was done. We removed the spacer while preserving the membrane and filled the gap with iliac bone autograft and allograft mixture. Union was attained 56 weeks after stage 2. The patient and family are satisfied with the outcome. Masquelet technique is a promising technique with a good success rate for large bone defects, especially in infected bone cases. No need for microvascular and other specialized tools made Masquelet technique can be done in a low-resource setting.